Regulation of Arabidopsis Matrix Metalloproteinases by Mitogen-Activated Protein Kinases and Their Function in Leaf Senescence - Wu, Hongjiao; Si, Qi; Liu, Jianmin; Yang, Liuyi; Zhang, Shuqun; Xu, Juan (Frontiers in Plant Science, 2022)
Leaf senescence is a developmentally programmed cell death process that is influenced by a variety of endogenous signals and environmental factors. Here, we report that MPK3 and MPK6, two Arabidopsis mitogen-activated protein kinases (MAPKs or MPKs), and their two upstream MAPK kinases (MAPKKs or MKKs), MKK4 and MKK5, are key regulators of leaf senescence. Weak induction of constitutively active MAPKKs driven by steroid-inducible promoter, which activates endogenous MPK3 and MPK6, induces leaf senescence. This gain-of-function phenotype requires functional endogenous MPK3 and MPK6. Furthermore, loss of function of both MKK4 and MKK5 delays leaf senescence. Expression profiling leads to the identification of matrix metalloproteinases (MMPs), a family of zinc- and calcium-dependent endopeptidases, as the downstream target genes of MPK3/MPK6 cascade. MPK3/MPK6 activation-triggered leaf senescence is associated with rapid and strong induction of At3-MMP and At2-MMP. Expression of Arabidopsis MMP genes is strongly induced during leaf senescence, qualifying them as senescence-associated genes (SAGs). In addition, either constitutive or inducible overexpression of At3-MMP is sufficient to trigger leaf senescence. Based on these findings, we conclude that MPK3/MPK6 MAPK cascade and MMP target genes further downstream are involved in regulating leaf senescence in Arabidopsis.